Analysis of Effectiveness and Contribution of Advertisement Tax Collection on Original Regional Income - Ayi Astuti (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2020)
Advertisement tax is one of the potential regional revenues and can be collected efficiently, effectively and economically. Efforts to increase PAD can be done by increasing the effectiveness of local tax revenue from PAD sources especially advertisement tax. This research of advertisement tax collection on PAD in Bandung City and to determine the contribution of the realization of advertisement tax revenue in an effort to increase the original income of the city of Bandung in 2013 and 2017. This research is a descriptive verification study with a quantitative approach. The data used are secondary data by type and time series during the period of 2013 to 2017. Data analysis was performed through correlation coefficients, simple linear regression analysis, coefficient of determination analysis and hypothesis testing (t test). Correlation coefficient analysis results show that the analysis of the effectiveness and contribution of advertisement tax has a significant effect on the Original Local Revenue at the Bandung City Tax Service.